Fermentation of Soybean Seed Husks (Glycine max L.) using Various Doses of Microbacter Alfaafa-11 (MA-11) and its Effect on Nutrient Content - Ahmad, Fandi; Mulyono, Ali Mursyid Wahyu; Windyasmara, Ludfia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Tempeh is the main product, while soybean husk is a solid waste from the tempeh making process. Soybean husk can be used as a substitute feed for whole or partial concentrate to stimulate growth. The purpose of this study was to determine the changes in the nutritional content of fermented soybean husk (FSSH) using Microbacter Alfaafa-11 (MA-11) with various doses. This study used different concentrations of Microbacter Alfaafa-11 (MA-11) to ascertain changes in the nutritional content of fermented soybean husk (FSSH). Utilizing a completely randomized design (CRD), three repetitions of each of the four treatment kinds were made of the methodology. The medication was administered as a series of MA-11 dosages, with the following amounts included: 0% (control), 0.05%, 0.10%, and 0.15%. The dry matter yield of FSSH, crude fiber content, and crude protein content were the variables that were observed. According to the study's findings, using MA-11 could considerably raise the crude protein content of FSSH (P<0.05) and greatly lower its dry matter yield (P<0.05), but it had no significant influence (P>0.05) on the crude fiber content of FSSH. The conclusion is that fermentation of soybean husks (Glycine max L.) using Alfalfa-11 Microbacteria does not have a significant effect on crude fiber content, but has a significant effect on crude protein content and dry matter yield of fermented soybean husks.